World-System Approach to Marx’s Analysis of Social Stratification - Yudin*Gregory (Journal of Economic Sociology, 2010)
The paper analyzes the works linking Marx’s ideas and world-system theory. The author depicts the components of this approach and formats a new point of view toward social stratification. The advantages and disadvantages of this approach are under focus.